Poly-Tobacco Use among Young Adult Waterpipe Smokers: Insights from University Students in Three Eastern Mediterranean Countries. (1st October 2020) - Darawad, Muhammad W.; Rezk-Hanna, Mary; Alhussami, Mahmoud; Lee, Juhan; Mostafa, Aya; Abu-Rmeileh, Niveen; Kheirallah, Khalid; Salama, Mohammed; Nakkash, Rima; Saleh, Zeyad; Salloum, Ramzi
Abstract: Introduction: There is a tendency of waterpipe smokers to advance their practice toward concurrent use (poly-tobacco use) of other tobacco products and nicotine delivery systems. This study investigated poly-tobacco use among waterpipe smokers, and its effect on their quit intention. Methods: Descriptive cross-sectional design was utilized to recruit a convenience sample of university students who used waterpipe in three East Mediterranean countries. Using an internet-based survey, data were collected regarding participants' demographics, use of alternative tobacco products and nicotine delivery systems, and waterpipe quitting profile. Results: A total of 2290 students agreed to participate, among which 1116 (45.3%) reported using at least one tobacco product beside waterpipe. Poly-tobacco use was highest (61.1%) in Egypt, followed by Jordan (45.1%) and Palestine (33.1%). Across countries, cigarettes were the most common product (45.2%, n = 924) followed by cigar (18.6%, n = 374) and e-shisha (17.5%, n = 353). Conversely, the least reported product was smokeless tobacco (7.5%, n = 151) preceded by regular pipe (9.5%, n = 193). Participants who were males (OR = 2.83, 95% CI: 2.18–3.65), older (22–29 years) (OR = 1.15, 95% CI: 1.09–1.22), unemployed (OR = 1.58, 95% CI: 1.22–2.04), and those who initiated waterpipe at a younger age (OR = 0.87, 95% CI: 0.87–0.91) had higher odds of being poly-smokers. Poly-tobacco users were significantly more resistant to quit waterpipe. Conclusion: This study demonstrates poly-tobacco use as a rising phenomenon among waterpipe smokers and highlights the necessity for initiating advanced interventions to help waterpipe poly-tobacco users quit this dangerous type of addiction. Various country-specific programs are needed considering the various products used by the users.